2022
DOI: 10.1186/s12883-022-02884-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sexual dysfunction in patients with multiple sclerosis: a perspective from neurologist

Abstract: Background Sexual dysfunction (SD) is a common comorbidity in people with multiple sclerosis (pwMS). It affects the quality of life and remains an overlooked condition. The objective of this study was to describe how Colombian neurologists assess and treat SD and explore the barriers during sexual function evaluation. Methods In this observational cross-sectional study we developed a questionnaire for neurologists with 4 sections (demographic data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Namely, our results showed that both illness perceptions and depressive symptoms can influence sexual dysfunction in pwMS, particularly when the disability is not severe, suggesting that helping pwMS process these dimensions may promote sexual health and well-being. Because sexual dysfunction is known to be inadequately addressed by clinicians working with pwMS [ 41 ], clinicians should first integrate sexual dysfunction assessment into their clinical approach [ 42 ]. In the case of sexual functioning impairment and after biological causes have been ruled out, clinicians should assess the potential role of illness perceptions and depressive symptoms in determining this impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, our results showed that both illness perceptions and depressive symptoms can influence sexual dysfunction in pwMS, particularly when the disability is not severe, suggesting that helping pwMS process these dimensions may promote sexual health and well-being. Because sexual dysfunction is known to be inadequately addressed by clinicians working with pwMS [ 41 ], clinicians should first integrate sexual dysfunction assessment into their clinical approach [ 42 ]. In the case of sexual functioning impairment and after biological causes have been ruled out, clinicians should assess the potential role of illness perceptions and depressive symptoms in determining this impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Altman and colleagues, in which MS doctors were surveyed regarding their approach to taking a sexual history of their patients, only 15% reported discussing sexuality with every patient. The lack of evaluation of SD during consultation leads to the remaining as an underdiagnosed and undertreated condition [91]. The most common reason for not doing so was a fear of crossing personal boundaries, lack of spontaneous communication by patients [92] or lack of knowledge [93].…”
Section: Discussionmentioning
confidence: 99%